Norms of Punishment in the General Population - Stefania Bortolotti; Marco Casari; Francesca Pancotto (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
Norms of cooperation and punishment differ across societies, but also within a single society. In an experiment with two subject pools sharing the same geographical and cultural origins, we show that opportunities for peer punishment increase cooperation among students but not in the general population. In previous studies, punishment magnified the differences across societies in peoples ability to cooperate. Here, punishment reversed the order: with punishment, students cooperate more than the general population while they cooperate less without it. Our results obtained with students cannot be readily generalized to the society at large.
Keywords: C72; C90; Z13; 330